Designing of Work Facility for Ecobrick Material Using Ergonomic Intervention to Reduce Muscoloskeletal Disorder - Tri Budiyanto; Hayati Mukti Asih; Okka Adiyanto; Irvan Kristanto (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Kamulyan waste bank is a place to collect the waste from the household around Lowanu Village, Brontokusuman, Mergangsan, Yogyakarta. This waste is distributed to garbage collectors and sorted. Plastic waste that cannot be recycled is used as material for making ecobricks. Ecobricks are materials made from used plastic bottles filled with plastic sachets, plastic bags, and similar materials that are compressed. In making ecobricks, workers perform activities in a sitting position on the floor with both legs folded in and a slightly bent posture. This work attitude causes muscle complaints in the upper and lower neck, upper arm, right elbow, left wrist, and left hand. The purpose of the study was to improve work attitudes to reduce muscle complaints in body parts by designing ergonomic work facilities. This research was conducted with ergonomics intervention on the design of ecobrick plastic compaction work facilities with the Nordic Body Map-VAS Modified Questionnaire. The muscle complaints of the workers' body parts were determined using the Nordic Body Map questionnaire. The results of the study provide a design for compaction of ecobrick plastic materials with dimensions of table length 134.44 cm, table width 66.39 cm, table height 71.63 cm, length of seat mat 41.41 cm, width of seat mat 43.49 cm, height seat 44.51 cm, backrest height 55.5 cm, and backrest width 45.88 cm. Based on the NBM-VAS questionnaire, it shows that the initial condition of pain or pain in the upper neck and lower neck with a moderate pain value is aimed at a scale of 6.5 cm and 7.3 cm to mild pain with a scale of 4.2 cm and 4.3 cm. . Moderate pain in the left wrist and left hand with a scale of 6.1 cm, respectively, to no pain on a scale of 3.1 cm and 3 cm.